(3OjhGf GdCHjhQOj (B((3GdfLOjGJ(B) (3GdbSe GdKGfjs - (3CHhGdeXaQ eMeO Hf CMeO Hf eMeO Hf eYGhjI GdCUZQ GdCehj GdCHjhQOj,J (B557 (3g` s
(3ChdgG (B:s
(3Ef CMb eG JUQa Edjg dge MeO ddg SHMGfg Ydi eG jJfGUQ ef fYe RgQI GdQjGV s
(3BNQgG (B:s
(3ef bUjOI dGejI(B: (3Rfj Gdbhe MJi JYQaj YfO hRfge EPG QaY GdejRGf cja Cejd s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3YdjgG SeGY ef CHj SYO CMeO Hf eSYhO GdeaJj GdHNGQj Edi MGeO eMehO Hf eMeO Hf CMeO Gdecj GdNNfOjs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs